Mutual fund size versus fees: International evidence - Miguel, A.; A. Keswani; Ramos, S. (Mutual fund size versus fees: International evidence, 2017)
In this paper, we use a comprehensive dataset of equity mutual funds covering 31 countries to study the effects of mutual fund size on fund total shareholder costs. We show that the level of total shareholder costs vary substantially for funds with different assets under management not only across countries but also within countries. We also show that competition in the fund industry explain these differences. In countries with more competitive fund industries total shareholder costs decline as funds get larger while in countries where there is little competition in the fund industry fund size increases total shareholder costs.